The Influence of Quality Assurance and Supportive Supervision on the Quality of Medical Care in Children's Hospitals of the Municipal Level of the Rostov Region - Tatiana V. Kulichenko; Alexander A. Baranov; Leyla S. Namazova-Baranova; Svetlana A. Mukhortova; Svetlana G. Piskunova; Elena A. Besedina; Dmytrij V. Prometnoy (Union of pediatricians of Russia, 2017)
Background. Improving the quality of medical care is the absolute priority of the World Health Organization and all socially-oriented ministries and departments around the world.Objective. Our aim was to evaluate the effectiveness of quality  assurance and supportive supervision in municipal hospitals to improve the quality of medical care for children (by the example of the Rostov region).Methods. The open observational study included 10 second-level hospitals in the Rostov Region. At the start of the project, the quality of inpatient care for children in the region was audited based on recommendations and tools of the World Health Organization, and training of medical personnel was organized. Monitoring visits to hospitals were carried out by experts every 3 months (supportive supervision). Reaudit of the quality of care was conducted a year later.Results. As a result of regular quality assurance and supportive supervision of hospitals during the first year of operation, such indicators of the quality of medical care as the availability of medical equipment for emergency care for children, the infrastructure of children's departments, the triage and provision of emergency care in children's departments, managing patients with various acute conditions (fever, diarrhea, respiratory diseases), supporting care, internal quality assurance, accessibility to standards of care and clinical guidelines for the diagnosis and treatment of various diseases, respect for children's rights were significantly (p < 0.05) improved.Conclusion. Supportive supervision and regular external quality assurances of hospitals contribute to a rapid increase in the quality of medical care for children.